Hydroxylation of pendant vinyl groups of poly(3-hydroxy undec-10-enoate) in high yield - EROĞLU, MEHMET SAYIP (WILEY-BLACKWELL, 2005)
Poly(3-hydroxy undec-10-enoate) (PHU) was synthesized by feeding Pseudomonas oleovarans with 10-undecenoic acid and nearly 100%, hydroxylation of double bonds of PHU was achieved by hydroboration-oxidation reaction using 9-borobicyclononane. The disappearance of vinyl signals of PHU in proton and C-13 NMR spectra was observed. Acetylation of hydroxylated PHU was conducted for molecular weight measurements. Molecular weight and polydispersity of hydroxylated PHU were found to be 10,000 and 1.23, respectively, while that of the originals was 32,000 and 2.42. Decomposition temperatures of original and hydroxylated PHU were 280 and 200 degrees C, respectively. (C) 2005 Wiley Periodicals, Inc.
Keywords: PHU; PHAs; biopolyesters; UNSATURATED SIDE-CHAINS; BACTERIAL POLYESTERS; PSEUDOMONAS-OLEOVORANS; CROSS-LINKING; EPOXIDATION; POLY-3-HYDROXYALKANOATES; BIOSYNTHESIS; ACIDS; UNITS